Ultrafast-switching of an all-solid-state electric double layer transistor with a porous yttria-stabilized zirconia proton conductor and the application to neuromorphic computing - Takayanagi, Makoto; Nishioka, Daiki; Tsuchiya, Takashi; Imura, Masataka; Koide, Yasuo; Higuchi, Tohru; Terabe, Kazuya (Materials today advances, 2023)
All-solid-state electric double layer transistors (ASS-EDLTs) have recently been attracting attention because of their huge potential for use in neuromorphic device applications. However, their low switching response speed is a significant drawback to their practical application. Here, we demonstrate ultrafast-switching of ASS-EDLTs, which was achieved by an excellent combination of hydrogenated diamond single crystal and a porous yttria stabilized zirconia thin film with extremely high proton conductivity. The switching response speed was investigated in response to gate voltage pulses. We achieved the ASS-EDLT that can operate at a very short response time of less than a hundred μs (i.e., 27 μs), even at room temperature. This is a far shorter time than that found in typical conventional ASS-EDLTs, which characteristically have response times measured in milliseconds or longer. Furthermore, the subject ASS-EDLT possessed characteristics that are similar to those of volatile memory devices. To demonstrate neuromorphic computing capability of the device, waveform transformation task has been performed. The results indicated that the ASS-EDLT, with its high operating speed, can contribute to the development of high-speed neuromorphic systems.